Cytotoxic activity of luvunga scandens plant on human cancer cell lines - Al Zikri, Putri Nurhidayah; Bakhtiar, M. Taher; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari (2014)
Luvunga scandens is a plant species belongs to the family of Rutaceae which come from the same family as citrus. Only a few studies on antifungal and insecticidal activities of L. scandens have been reported [1]. Yet, no study have reported the cytotoxic activity of this plant. Based on the traditional usage, stem of L. scandens via decoction was taken orally to treat malarial fever and tiredness [2;3]. Hence, this study is the first report on cytotoxic activity and phytochemical screening of the species of L. scandens. The aim of this study was to investigate the phytochemical and cytotoxic activity of the leaf and stem extract of L. scandens plant. Extracts of the leaf and stem were obtained from sequential extraction procedures by various organic solvents. All extracts were subjected to phytochemical screening to identify the chemical constituents and cytotoxic activities by 3-(4, 5-dimethylthaizol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay to determine the viability of cells. The result shows that the stem and leaf extracts of L. scandens were found to be responsible for the cytotoxic effects based on the dose-response inhibition. The IC50 value of extracts from leaf of L. scandens; LSC-LD and LSC-LM against MCF-7 cell line were 62.5 μg/mL and 80.0 μg/mL respectively. Whereas the IC50 value of extracts from stem of L. scandens; LSC-SD and LSC-SM were 75.0 μg/mL and 77.0 μg/mL respectively. For A549 cell line, all extracts exhibit dose-response inhibition but not able to reduce the percentage of cell viability to 50 %. So, the IC50 cannot be extrapolated. In conclusion, this present study demonstrates that all extracts of L. scandens exhibit cytotoxic activities with dose-response inhibition against MCF-7 and A549 cell lines. It therefore revealed that L. scandens is a potential source of cytotoxic agent.